2022
DOI: 10.21273/hortsci16402-21
|View full text |Cite
|
Sign up to set email alerts
|

Cut-flower Carnation Photoluminescence: Potential New Value-added Product

Abstract: Success of the floral industry lies in strengthening the fresh flower market with value-added products. An experiment was conducted to quantify luminescence of cut-flower white carnations after exposure to two fluorescent products (dye from a yellow highlighter or glow-in-the-dark spray paint). Single stems were placed in bud vases that were filled with 240 mL deionized water and 2 g floral preservative. Highlighter treatments were applied to the vase as either one drop, three drops, or half of the dye reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…Stem fresh weight, relative stem fresh weight, flower diameter, and overall solution absorption rate increased each day and peaked on 4 DAT; thereafter, a steady decline occurred (Table 1). Pace et al (2022) also reported similar results for carnation using yellow highlighter and green glow-in-the-dark paint. Daily solution absorption was negative for the first 4 DAT before increasing to positive and significantly greater values from 5 DAT through 10 DAT.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Stem fresh weight, relative stem fresh weight, flower diameter, and overall solution absorption rate increased each day and peaked on 4 DAT; thereafter, a steady decline occurred (Table 1). Pace et al (2022) also reported similar results for carnation using yellow highlighter and green glow-in-the-dark paint. Daily solution absorption was negative for the first 4 DAT before increasing to positive and significantly greater values from 5 DAT through 10 DAT.…”
Section: Resultssupporting
confidence: 60%
“…Measurements were performed daily to obtain the stem weight (combined weight of stem and flower), vase weight, average flower diameter (average of two perpendicular measurements), and visual deterioration. The relative fresh weight percent, water content, flower diameter change rate, overall solution absorption rate, and daily solution absorption rate were calculated according to Pace et al (2022). Visual deterioration was evaluated using a rating score (average daily rating per day) of 1 to 4 for deterioration (1, no browning; 2, browning around the edges; 3, some browning throughout the flower; 4, complete browning and shriveled flower) to represent the quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Tekli c et al ( 2003) reported a continuous decrease in floral diameter over the course of their temperature study for each rose and carnation cultivar. In other studies, Pace et al (2022aPace et al ( , 2022b and Kumari et al (2018) suggest the decrease in floral diameter mid way through the useful life of the flower is due to the treatment effects of color tinting.…”
Section: Resultsmentioning
confidence: 93%
“…Various studies have researched and incorporated luminescence in root tissues, leaves and fruits, ceramic surfaces, fabrics, and information encryption (Defrianto et al 2022;Gao et al 2009;Khattab et al 2018;Strock et al 2019;Swathi et al 2023). The persistent luminescence of cut flowers has recently been reported using green luminescence by means of glow-in-the-dark spray paint and highlighters (Pace et al 2022b) and blue luminescence by dip and spray of using a blue glowin-the-dark powder in a water-based solution (Pace et al 2022a). Both studies were limited to white carnation flowers and solely tested green and blue colored luminescence.…”
mentioning
confidence: 99%